PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) MELALUI KEGIATAN MEMBATIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ASAM BASA - Rabiah Afifah Daulay; Syifa Nabila Lubis; Dira Khairunisa; Andin Livia Siagian; Naffa Sati; Zaskia Shalwa Dina; Fahrezi Hasyim Said (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve students' learning outcomes on acid-base material through the implementation of the Project Based Learning (PjBL) model integrated with batik-making activities. The study employed Classroom Action Research consisting of two cycles, namely planning, implementation, observation, and reflection. The subjects were students of class XI-4 SMA Negeri 1 Tanjung Morawa. Data were collected through pretest and posttest instruments and analyzed using normalized gain (N-Gain). The results showed that the average score increased from 57.50 to 70.60 in cycle I with an N-Gain value of 0.46 (moderate category). In cycle II, the average score increased from 55.42 to 91.04 with an N-Gain value of 0.76 (high category). These findings indicate that Project Based Learning integrated with batik activities can effectively improve students' learning outcomes and create a contextual and meaningful learning process.